MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENGATASI KESULITAN BELAJAR MAHASISWA BERBAHASA INGGRIS BIDANG EKONOMI DALAM MEMPERSIAPKAN ENTEPRENUER HANDAL - Nila Afningsih (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2018)
In general, students still have difficulty to convey ideas, thoughts, questions and so on in the language, especially in English. The students have to prepare themselves before going directly to the job market. One of the efforts that can be used as an alternative problem solving is to apply Problem Posing Model based on contextual.This research is also an effort to overcome the difficulties of students in English in order to prepare themselves as a reliable entrepreneurs needed by the world economy of this country or even the international world. This research was conducted on Economics Faculty student UMN Al-Washliyah Medan.After doing this research, we got positive results from the students. Students have more confidence in English as their capital to prepare a reliable entrepreneur. This research does not stop until it is only because of the results of this research will be published in the form of journal articles, proceedings, and textbooks that can be used by students, especially English Business subjects.